Integrated nimo w catalytic coating co2 capture catalytic packing and electroplating preparation process

CN122974333APending Publication Date: 2026-10-27CHINA UNIV OF MINING & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611166215.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

第一,催化剂与填料分离导致传质效率受限

Benefits of technology

1、本发明通过NiMoW三元合金催化涂层的B/L酸位点协同催化作用,富CO2胺溶液的解吸温度可降至90~100℃,优选95℃,较传统热解吸工艺(>120℃)降低25℃以上,从根本上减少了高温解吸带来的溶剂降解和二次气溶胶污染问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974333A_ABST
    Figure CN122974333A_ABST
Patent Text Reader

Abstract

The application discloses a kind of integrated NiMoW catalytic coating CO2 capture catalytic packing and electroplating preparation process, belong to CO2 capture and emission reduction technical field.The packing is stainless steel structured packing as matrix, by electroplating process on its surface deposition NiMoW ternary alloy catalytic coating, with amorphous / nanocrystalline structure and proportion suitable Brønsted / Lewis acid site, with high catalytic activity, strong matrix binding force and excellent corrosion resistance.The packing is applied to chemical absorption method CO2 capture desorption process, and the desorption temperature can be reduced to 95 DEG C, and the CO2 desorption rate is increased by 184% compared with blank system, and the regeneration energy consumption is as low as 2.2GJ / t CO2, the coating is continuously stable for more than 500 hours without falling off and no obvious corrosion, effectively solve the technical problems of traditional carbon capture technology, such as high desorption temperature, high energy consumption and easy corrosion of packing, suitable for industrial scale carbon capture application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon dioxide capture and emission reduction technology, specifically relating to an integrated NiMoW catalytic coating for CO2 capture catalytic packing and its electroplating preparation process, as well as its application in the chemical absorption carbon capture process for low-energy catalytic desorption and regeneration of CO2-rich organic amine solutions. Background Technology

[0002] Chemical absorption is one of the most mature and widely used CO2 capture technologies. Using organic amine solutions such as monoethanolamine (MEA) and methyldiethanolamine (MDEA) as absorbents, it has been demonstrated on a large scale in coal-fired power plants, steel, cement, and chemical industries. However, the core bottleneck of this technology lies in the fact that the regeneration process of the CO2-rich amine solution requires thermal desorption at temperatures above 120°C. Solvent regeneration energy consumption accounts for more than 60% of the total energy consumption of the carbon capture process, and desorption energy consumption is as high as 3.6~4.0 GJ / tCO2, severely restricting the economic feasibility and large-scale application of carbon capture technology.

[0003] To address the aforementioned high energy consumption issue, scholars both domestically and internationally have proposed a catalytic desorption technology route. This involves introducing solid acid catalysts during the desorption process to accelerate proton transfer and lower the C-N bond breaking energy barrier, thereby achieving efficient CO2 desorption at lower temperatures. Existing solid acid catalysts, such as molecular sieves, metal oxides, and solid superacids, can reduce the CO2 desorption temperature and increase the desorption rate to some extent. For example, solid acid catalysts based on BAS-LAS ​​acid site regulation can reduce desorption energy consumption to approximately 2.2 GJ / tCO2. From a catalytic mechanism perspective, Brønsted acid sites (BAS) act as proton donors to promote the deprotonation of protonated amines, while Lewis acid sites (LAS) promote the breaking of C-N bonds in carbamates. The catalytic performance is optimal when both coexist in an appropriate ratio, with the best catalytic activity observed when the B / L ratio is close to 1.

[0004] However, existing catalytic desorption technologies still have many prominent problems: First, the separation of catalyst and packing material limits mass transfer efficiency. Existing catalysts are mostly packed in column form or set up in independent catalyst beds. The catalytic function and the mass transfer function of the structured packing material are independent of each other. The contact efficiency between CO2-rich liquid and catalytic active sites is low, and particulate catalysts are prone to clogging packing channels, increasing the pressure drop in the column.

[0005] Second, the bonding strength of the catalyst coating is insufficient. Existing methods for loading catalytic coatings onto the filler surface, such as in-situ growth and impregnation calcination, result in weak adhesion between the coating and the substrate. Under long-term high-temperature amine immersion and fluid scouring conditions, the coating is prone to detachment, resulting in a limited service life. Laser etching modification only optimizes the surface structure and does not load a catalytic coating, thus offering limited improvement in catalytic performance.

[0006] Third, there is a lack of coating systems that combine catalytic activity and corrosion resistance. The pH of organic amine solutions decreases and their corrosiveness increases after absorbing CO2, which can cause severe corrosion to stainless steel packing. However, existing catalytic coating designs only focus on catalytic activity and neglect corrosion protection, leading to easy corrosion failure of the packing during long-term operation.

[0007] Fourth, the desorption temperature is still too high and the improvement in desorption rate is limited. The desorption temperature of existing catalytic desorption technologies is generally above 98~105℃, and the improvement in desorption rate is mostly between 40% and 120%. The regeneration energy consumption is still difficult to meet the low energy consumption requirements of industrial carbon capture.

[0008] Therefore, developing integrated catalytic packing materials that combine high catalytic activity, excellent bonding strength, superior corrosion resistance, and long-term operational stability to achieve efficient desorption at lower temperatures and significantly reduced energy consumption is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0009] The purpose of this invention is to overcome the shortcomings of the prior art and provide an integrated NiMoW catalytic coating CO2 capture catalytic filler and electroplating preparation process, which realizes efficient desorption of CO2 at a low temperature of 95℃, significantly improves the desorption rate, reduces regeneration energy consumption, and at the same time ensures high bonding strength between the coating and the substrate, excellent corrosion resistance, and long-term stable operation.

[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows: On the one hand, the present invention provides an integrated NiMoW catalytic coating CO2 capture catalytic packing, comprising a stainless steel structured packing substrate and a NiMoW ternary alloy catalytic coating deposited on the surface of the structured packing substrate by an electroplating process; wherein the NiMoW ternary alloy catalytic coating has a Ni mass percentage content of 55-75%, a Mo mass percentage content of 15-30%, and a W mass percentage content of 4-15%.

[0011] Furthermore, the NiMoW ternary alloy catalytic coating has an amorphous or nanocrystalline microstructure, and the coating surface contains abundant Brønsted and Lewis acid sites, with a ratio of Brønsted to Lewis acid sites of 0.8–1.2. The strength and distribution of acidic sites in the catalytic coating can be controlled by the elements Mo and W, and synergistic catalysis of the two acid sites can be achieved by optimizing the ratio of Ni, Mo, and W.

[0012] Furthermore, the bonding strength between the NiMoW ternary alloy catalytic coating and the structured filler matrix is ​​not less than 45 MPa; the coating corrosion current density measured in a 5 wt% NaCl solution is not higher than 8 × 10⁻⁶ MPa. -6 A / cm 2 .

[0013] Furthermore, the stainless steel structured packing matrix is ​​a stainless steel corrugated plate structured packing with a three-dimensional corrugated structure, and the material is selected from 316L stainless steel, 304L stainless steel or 2205 duplex stainless steel, with a specific surface area of ​​250~750m². 2 / m 3 The thickness of the NiMoW ternary alloy catalytic coating is 15~50μm.

[0014] On the other hand, the present invention provides a method for preparing the above-mentioned CO2 capturing catalytic packing, comprising the following steps: S1. Pretreatment of structured packing matrix: The stainless steel structured packing is sequentially subjected to alkaline washing to remove oil, acid washing to activate, deionized water rinsing, and then dried for later use.

[0015] S2. Preparation of Electroplating Solution: The electroplating solution consists of: nickel sulfate (NiSO4·6H2O) 60~120g / L, sodium molybdate (Na2MoO4·2H2O) 20~50g / L, sodium tungstate (Na2WO4·2H2O) 10~35g / L, sodium citrate (Na3C6H5O7·2H2O) 60~100g / L as a complexing agent, ammonia (NH3·H2O, 25~28wt%) 10~30mL / L as a pH adjuster and auxiliary complexing agent, sodium saccharin (C7H3NNaO3S) 1~5g / L as a stress reliever, and sodium dodecyl sulfate (C 12 H 25 NaO4S (0.1~0.5 g / L) was used as a surfactant. Deionized water was used for preparation, and the pH was adjusted to 8.5~10.5 with ammonia.

[0016] S3. Electroplating deposition: Using pretreated stainless steel structured filler as the cathode and nickel plate as the anode, the area ratio of the cathode to the anode is 1:1 to 1:2. The cathode and anode are immersed in the electroplating solution, and electroplating deposition is performed using direct current or pulsed current.

[0017] S4. Post-treatment: After electroplating, the filler is removed, rinsed to remove residual plating solution, and heat-treated at 200~400℃ for 1~4 hours under inert atmosphere or vacuum conditions. Then, it is cooled to room temperature in the furnace to obtain the integrated CO2 capture and catalytic filler.

[0018] Further, in step S1, the alkaline washing uses a mixed solution of NaOH and Na2CO3 with a total concentration of 40~80 g / L, a treatment temperature of 60~80℃, and a treatment time of 10~30 min; the acid washing activation uses a sulfuric acid or hydrochloric acid solution with a mass fraction of 1~10%, a treatment temperature of room temperature to 50℃, and a treatment time of 1~5 min.

[0019] Furthermore, when DC electroplating is used in step S3, the cathode current density is 2~8 A / dm.2 4~6A / dm is preferred 2 The electroplating solution temperature is 40~65℃, preferably 50~55℃; the electroplating time is 30~120min; mechanical stirring or solution circulation is used during the electroplating process, with a stirring speed of 100~300rpm. When pulse electroplating is used, the peak pulse current density is 4~15A / dm³. 2 The duty cycle is 20-60%, and the pulse frequency is 50-500Hz.

[0020] Furthermore, step S4 is followed by step S5, which involves surface activation treatment: immersing the heat-treated filler in a 0.1-1.0 mol / L dilute sulfuric acid solution at room temperature for 0.5-1 hour, then rinsing it with deionized water until neutral and drying it to enhance the exposure of acidic sites on the coating surface and its catalytic activity.

[0021] Thirdly, the present invention provides the application of the above-mentioned CO2 capture catalytic packing in the chemical absorption carbon capture process: the CO2 capture catalytic packing is filled into a CO2 desorption tower to form a catalytic desorption packing layer, and then a rich organic amine solution (CO2 loading of 0.3~0.6 mol CO2 / mol amine) that has absorbed CO2 is introduced into the upper part of the desorption tower. Under the action of gravity, the rich solution flows downward along the surface of the CO2 capture catalytic packing in a liquid film form; the steam generated by the reboiler at the bottom of the desorption tower passes through the packing layer from bottom to top and comes into countercurrent contact with the rich solution to carry out heat and mass transfer. Under the action of the NiMoW catalytic coating, the rich solution undergoes a catalytic desorption reaction, releasing CO2 gas and regenerating the organic amine solution.

[0022] Furthermore, the CO2 loading of the organic amine-rich solution is 0.3~0.6 mol CO2 / mol amine; the desorption tower operating conditions are: desorption temperature 90~100℃, preferably 95℃; tower top pressure 0.1~0.2MPa; liquid spray density 5~20m³ / min. 3 / (m 2 ·h).

[0023] The mechanism of catalytic desorption is as follows: Brønsted acid sites on the surface of the NiMoW catalytic coating provide protons to the protonated amine, promoting the deprotonation of the protonated amine; at the same time, Lewis acid sites coordinate with the carbonyl oxygen in the carbamate, weakening the C-N bond energy and promoting the decomposition of the carbamate; the two acid sites work synergistically to achieve efficient CO2 desorption at a low temperature of 95℃.

[0024] Compared with the prior art, the present invention has the following advantages: 1. This invention utilizes the synergistic catalytic effect of the B / L acid sites in the NiMoW ternary alloy catalytic coating to reduce the desorption temperature of CO2-rich amine solutions to 90~100℃, preferably 95℃, which is more than 25℃ lower than the traditional thermal desorption process (>120℃). This fundamentally reduces the solvent degradation and secondary aerosol pollution problems caused by high-temperature desorption.

[0025] 2. Under desorption conditions of 95℃, the CO2 desorption rate of this invention is increased by 184% compared with the blank control without catalyst, which is significantly higher than the improvement of existing catalysts; through the synergistic regulation of Mo and W elements, the B / L acid site ratio is optimized to 0.8~1.2, achieving highly efficient synergistic catalysis.

[0026] 3. This invention reduces CO2 desorption energy consumption to 2.2 GJ / tCO2 through low-temperature and high-efficiency catalytic desorption, which is only 55% to 61% of the energy consumption of traditional thermal desorption, effectively breaking through the bottleneck of high energy consumption in carbon capture technology.

[0027] 4. This invention uses an electroplating process to deposit a NiMoW alloy coating in situ on a structured filler substrate. The coating and the substrate form a metallurgical bond with a bonding strength of not less than 45MPa. It can operate continuously and stably for more than 500 hours without peeling off, thus solving the technical problem of easy peeling off of traditional coatings.

[0028] 5. The NiMoW ternary alloy coating prepared by this invention has excellent corrosion resistance to high-temperature amine solutions containing CO2. The addition of W element further enhances the chemical stability of the alloy in alternating acid and alkali media. Compared with uncoated 316L stainless steel filler, the corrosion rate is reduced by more than 90%, which greatly extends the service life of the filler.

[0029] 6. The catalytic coating of the present invention is directly constructed on the surface of the structured packing, realizing the integration of catalytic function and mass transfer function, maximizing the contact area between the catalyst and the rich liquid, significantly improving the mass transfer efficiency, and avoiding the problems of increased pressure drop and channel blockage caused by particulate catalyst filling.

[0030] 7. The electroplating preparation method of the present invention is mature and has good controllability. It is suitable for regular fillers of various specifications and shapes, and is convenient for large-scale industrial production and promotion. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of the preparation process of the CO2 capture catalytic packing material of the present invention.

[0032] Figure 2 This is a schematic diagram of the overall structure of the CO2 capture catalytic packing material of the present invention.

[0033] Figure 3This is a schematic diagram of the single-piece structure of the CO2 capture catalytic packing material of the present invention, wherein 11 is a stainless steel substrate and 12 is a NiMoW catalytic coating.

[0034] Figure 4 This is a schematic diagram of the electroplating process apparatus of the present invention, wherein 1 is a single-piece filler cathode, 2 is a nickel counter electrode, 3 is an electrolyte, 4 is a stirring magnet, and 5 is an electrolytic cell.

[0035] Figure 5 The image shows the pyridine adsorption infrared spectrum (Py-IR) of the NiMoW catalytic coating prepared in Example 1.

[0036] Figure 6 This is a comparison graph of CO2 desorption rates between Example 1 and the blank control group (desorption temperature 95℃).

[0037] Figure 7 The images shown are SEM images of the CO2 capture catalytic packing material before and after operation in Example 1, where (a) is before the reaction and (b) is after 500 hours of continuous operation. Detailed Implementation

[0038] The present invention will be further described below.

[0039] Example 1: As Figure 1 As shown, the specific steps are as follows: S101. Packing Pretreatment: Select 316L stainless steel corrugated plate structured packing with a three-dimensional corrugated structure (specific surface area 500 m²). 2 / m 3 The sample blocks were cut into 100mm × 100mm pieces. The sample blocks were immersed in an alkaline washing solution containing 50g / L NaOH and 30g / L Na2CO3 and treated at 70℃ for 20min to degrease and remove oil. After removal, they were rinsed with deionized water and then immersed in a 2% hydrochloric acid solution and activated at room temperature for 5min. After removal, they were rinsed with plenty of deionized water and dried with cold air for later use.

[0040] S102. Electroplating solution preparation: Prepare 1L of electroplating solution according to the following composition: 90g nickel sulfate (NiSO4·6H2O), 35g sodium molybdate (Na2MoO4·2H2O), 18g sodium tungstate (Na2WO4·2H2O), 80g sodium citrate (Na3C6H5O7·2H2O), 20mL 25% ammonia water (NH3·H2O), 2g sodium saccharin (C7H3NNaO3S), and sodium dodecyl sulfate (C... 12 H 25 Add 0.3g of NaO4S to deionized water and stir until completely dissolved. Adjust the pH to 9.5 with ammonia, bring the volume to 1L, and stir well.

[0041] S103, Electroplating Deposition: Using a pretreated 316L stainless steel filler sample as the cathode and a nickel plate with a purity ≥99.9% as the anode, the cathode to anode area ratio is 1:1.5. The electrodes are immersed in the electroplating solution, and a DC power supply is connected for electroplating. Process parameters: Cathode current density 5A / dm³ 2 The electroplating solution temperature was 52±2℃, the electroplating time was 60min, and the stirring speed was 200rpm.

[0042] S104. Post-treatment: After electroplating, remove the sample, rinse it thoroughly with deionized water, heat it to 350°C at 5°C / min under nitrogen atmosphere protection, hold it at that temperature for 3 hours, and then cool it to room temperature with the furnace.

[0043] S105, Surface Activation: Immerse the heat-treated sample in a 1 mol / L dilute sulfuric acid solution at room temperature for 2 minutes, remove and rinse with deionized water until neutral, then dry to obtain the CO2 capturing catalytic packing material as shown below. Figure 2 and Figure 3 As shown.

[0044] Coating characterization and performance testing: Composition and structure: ICP analysis showed that the coating contained 65.3 wt% Ni, 23.5 wt% Mo, and 10.8 wt% W. The coating thickness was approximately 28 μm. It was an amorphous / nanocrystalline mixed structure with a dense and uniform surface, free from cracks and pinholes.

[0045] Acid site characterization: such as Figure 5 As shown, Py-IR analysis revealed the presence of characteristic peaks for both Brønsted and Lewis acid sites in the coating, with a quantitative calculation showing a B / L acid site ratio of approximately 1.05.

[0046] Bond strength: Tested by tensile method according to ASTM C633 standard, the coating bond strength is 52 MPa.

[0047] Corrosion resistance: After immersion in 30wt% MEA solution (CO2 loading 0.5mol / mol) at 95℃ for 500 hours, the potentiodynamic polarization test showed a corrosion current density of 6.2×10⁻⁶. -6 A / cm 2 .

[0048] Catalytic desorption performance test: The prepared CO2 capture catalytic packing was packed into the packing layer of the desorption experimental apparatus. A 30wt% MEA aqueous solution was used as the absorbent, and the CO2-rich solution loading was 0.5 mol CO2 / mol MEA. The desorption temperature was controlled at 95℃, the column top pressure at 0.12 MPa, and the rich solution feed rate at 15 mL / min. Uncoated 316L stainless steel packing of the same specifications served as a blank control group. Figure 6As shown, the test results indicate that the CO2 desorption rate was increased by 184% compared to the control group, and the desorption energy consumption was only 2.2 GJ / tCO2.

[0049] Long-term stability test: The coating was continuously operated at 95℃ with a 30wt% MEA solution for 500 hours, with samples taken every 50 hours. Results showed that after 500 hours, the coating mass loss was only 2.3%, and there was no peeling, blistering, or cracking. The CO2 desorption rate remained above 89.7% of the initial rate throughout the 500-hour operation, demonstrating excellent long-term stability. Figure 7 As shown, scanning electron microscopy revealed no obvious corrosion pits or peeling on the coating surface, indicating that the NiMoW coating provides good corrosion protection to the substrate.

[0050] Example 2: Except for adjusting the sodium molybdate concentration in the electroplating solution to 25 g / L and the sodium tungstate concentration to 28 g / L, the preparation conditions and testing methods were the same as in Example 1. Tests showed that the CO2 desorption rate at 95℃ was 172% higher than the control group, with a desorption energy consumption of 2.3 GJ / tCO2; the coating adhesion strength was 49 MPa, and no significant peeling was observed after 500 hours of continuous operation.

[0051] Example 3: Except for adjusting the cathode current density to 7A / dm 2 Except for the electroplating time being shortened to 40 minutes, all other preparation conditions and testing methods were the same as in Example 1. Tests showed that the CO2 desorption rate at 95℃ was 176% higher than the blank group, with a desorption energy consumption of 2.25 GJ / tCO2; the coating adhesion strength was 48 MPa.

[0052] Example 4: Except for the filler matrix material being changed to 304L stainless steel, the preparation conditions and testing methods were the same as in Example 1. The coating adhesion strength was tested to be 50 MPa; under the same corrosion conditions, the corrosion current density was 7.1 × 10⁻⁶. -6 A / cm 2 The corrosion rate of the coated 304L stainless steel was reduced by more than 88%; the CO2 desorption rate at 95℃ was increased by 181% compared with the control group.

[0053] Comparative Example 1: Without electroplating, desorption experiments were conducted directly using untreated 316L stainless steel structured filler, with all other test conditions the same as in Example 1. The test results served as a blank baseline, showing the lowest desorption rate and a desorption energy consumption of approximately 3.8 GJ / tCO2.

[0054] Comparative Example 2: Preparation of NiMo oxide coating using the traditional impregnation-calcination method: The filler pretreated in Example 1 was immersed in a nitrate solution containing Ni and Mo, removed, dried, and calcined at 400°C for 2 hours. Other test conditions were the same as in Example 1. Test results: The CO2 desorption rate was increased by approximately 82% compared to the blank group; the coating bonding strength was only 12 MPa, and localized peeling occurred in less than 200 hours of operation.

[0055] Comparative Example 3: A NiMo binary alloy coating was prepared using the same electroplating process as in Example 1, but without sodium tungstate in the plating solution. All other test conditions were the same as in Example 1. Test results: The CO2 desorption rate was increased by approximately 138% compared to the blank group; the corrosion current density was 1.5 × 10⁻⁶. -5 A / cm 2 Its corrosion resistance is significantly lower than that of NiMoW ternary alloy coating.

[0056] Results Analysis: Based on the results of the above embodiments and comparative examples, it can be concluded that: 1. The NiMoW ternary alloy catalytic coating prepared by this invention has better catalytic activity and corrosion resistance than the NiMo binary coating. The introduction of W element not only enhances the corrosion resistance of the coating in CO2-containing amine solution, but also optimizes the distribution and intensity of surface acid sites, making the B / L acid site ratio closer to the optimal value, thus achieving more efficient catalytic desorption.

[0057] 2. The NiMoW coating prepared by the electroplating process of this invention has an optimal bonding strength (52 MPa) with the substrate that is much higher than that of the oxide coating prepared by the traditional impregnation-calcination method (12 MPa), which fundamentally solves the problem of easy coating peeling.

[0058] 3. The NiMoW ternary alloy catalytic coating of the present invention integrates catalytic desorption and corrosion protection functions, and has high catalytic activity, strong adhesion, excellent corrosion resistance and long-term stability, which can meet the long-term operation requirements of industrial carbon capture devices under harsh operating conditions.

[0059] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. An integrated NiMoW catalytic coating CO2 capture catalytic packing, characterized in that, It includes a stainless steel structured filler substrate and a NiMoW ternary alloy catalytic coating deposited on the surface of the structured filler substrate by an electroplating process; in the NiMoW ternary alloy catalytic coating, the mass percentage of Ni is 55-75%, the mass percentage of Mo is 15-30%, and the mass percentage of W is 4-15%.

2. The packing material according to claim 1, characterized in that, The NiMoW ternary alloy catalytic coating has an amorphous or nanocrystalline microstructure, and the coating surface contains both Brønsted acid sites and Lewis acid sites, with a ratio of 0.8 to 1.

2.

3. The packing material according to claim 1, characterized in that, The bonding strength between the NiMoW ternary alloy catalytic coating and the structured filler matrix is ​​not less than 45 MPa; the corrosion current density of the coating measured in 5 wt% NaCl solution is not higher than 8 × 10⁻⁶ MPa. - 6 A / cm 2 .

4. The packing material according to claim 1, characterized in that, The stainless steel structured packing matrix is ​​a stainless steel corrugated plate structured packing with a three-dimensional corrugated structure. The material is selected from 316L stainless steel, 304L stainless steel, or 2205 duplex stainless steel, and the specific surface area is 250~750m². 2 / m 3 ; The thickness of the NiMoW ternary alloy catalytic coating is 15~50μm.

5. A method for preparing the CO2 capture catalytic packing material according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Pretreatment of structured packing matrix: The stainless steel structured packing is sequentially subjected to alkaline washing to remove oil, acid washing to activate, deionized water rinsing, and then dried for later use. S2. Preparation of electroplating solution: The electroplating solution contains 60~120g / L nickel sulfate, 20~50g / L sodium molybdate, 10~35g / L sodium tungstate, 60~100g / L sodium citrate, 10~30mL / L ammonia, 1~5g / L sodium saccharin, and 0.1~0.5g / L sodium dodecyl sulfate. Adjust the pH value to 8.5~10.

5. S3. Electroplating deposition: Using pretreated stainless steel structured filler as the cathode and nickel plate as the anode, the cathode and anode are immersed in the electroplating solution, and electroplating deposition is carried out using direct current or pulsed current. S4. Post-treatment: After electroplating, the filler is removed, rinsed to remove residual plating solution, and heat-treated at 200~400℃ for 1~4 hours under inert atmosphere or vacuum conditions. Then, it is cooled to room temperature in the furnace to obtain CO2 capture catalytic filler.

6. The method according to claim 5, characterized in that, In step S1, the alkaline washing uses a mixed solution of NaOH and Na2CO3 with a total concentration of 40~80 g / L, a treatment temperature of 60~80℃, and a treatment time of 10~30 min; the acid washing activation uses a sulfuric acid or hydrochloric acid solution with a mass fraction of 1~10%, a treatment temperature of room temperature to 50℃, and a treatment time of 1~5 min.

7. The method according to claim 5, characterized in that, In step S3, when using direct current electroplating, the cathode current density is 2~8 A / dm. 2 The electroplating solution temperature is 40~65℃, the electroplating time is 30~120min, and stirring is maintained during the electroplating process at a speed of 100~300rpm; when pulse electroplating is used, the peak pulse current density is 4~15A / dm³. 2 The duty cycle is 20-60%, and the pulse frequency is 50-500Hz.

8. The method according to claim 5, characterized in that, It also includes step S5, surface activation treatment: immersing the heat-treated filler in a 0.1~1.0 mol / L dilute sulfuric acid solution for 0.5~1 hour at room temperature, then rinsing until neutral and drying.

9. The application of the CO2 capture catalytic packing material according to any one of claims 1-4 in a chemical absorption carbon capture process, characterized in that, A CO2-capturing catalytic packing is packed inside a CO2 desorption tower to form a catalytic desorption packing layer. Then, an organic amine-rich solution that has absorbed CO2 is introduced into the upper part of the desorption tower. The rich solution flows downward along the surface of the CO2-capturing catalytic packing and comes into countercurrent contact with the rising steam at the bottom of the tower. Under the action of the NiMoW ternary alloy catalytic coating, a catalytic desorption reaction occurs, releasing CO2 gas and regenerating the organic amine solution. The desorption temperature is 90~100℃.

10. The application according to claim 9, characterized in that, The CO2 loading of the organic amine-rich solution is 0.3~0.6 mol CO2 / mol amine; the top pressure of the desorption tower is 0.1~0.2 MPa, and the liquid spray density is 5~20 m³ / mol. 3 / (m 2 ·h).